Faktor-Faktor Penyebab Rendahnya Minat Siswa Terhadap Ekstrakulikuler Tari Di SMP Negeri 27 Padang - Annisa A Alzain; Susmiarti Susmiarti (Institut Nalanda, 2023)
The purpose of this study was to reveal and describe the factors that cause students' low interest in extracurricular dance at SMP Negeri 27 Padang. The type used in this research is qualitative research with descriptive method. The objects of this research were 18 students of class VII, VIII who participated in extracurricular dance. The research location is precisely at SMP Negeri 27 Padang on Jalan Air Paku, Sungai Sapih Village, Kuranji District, Padang City, West Sumatra Province. The types of data used are primary data and secondary data. The instrument in this study was the researcher himself and was assisted by camera support and stationery. The types of data used are primary data and secondary data. Data collection techniques were obtained from literature, observation, interviews and documentation. The data analysis technique used in this research is collecting data, identifying data, classifying data, drawing conclusions.The results showed that students' interest in dance extracurricular activities at SMP Negeri 27 Padang was low due to the lack of student motivation in extracurricular activities. The factors causing the low interest of students in extracurricular dance at SMP Negeri 27 Padang are influenced by two factors, namely internal factors and external factors.